Sistem Akuntansi Penjualan Kredit Koperasi Karyawan PT. PLN (Persero) Unit 3 Cirebon - Alitia Rachmawati; Widya Jati Lestari; Agus Sevtiana (Fakultas Ekonomi dan Bisnis, Universitas Catur Insan Cendekia, 2021)
Daya Lisna Sutera Cooperative is a cooperative for employees and retirees at PT. PLN (Persero) Service Unit 3 Cirebon. This cooperative is located at Jalan Tuparev No.100, Cirebon city. Members of this cooperative consist of active employees and retired employees of PLN 3 Cirebon service unit. Active employees are required to become members of the cooperative, while retired employees are not mandatory. This cooperative business activity accommodates members' deposits, distributes loans to members, provides credit sales of necessities for members, and provides vehicle rental services. There are still some company recording activities that are done manually, namely recording sales and savings and loans using the excel application. This study aims to create a credit sales accounting system that is expected to be better and more efficient, so that bookkeeping reports can be done faster and increase the effectiveness of the company, both from procedures, documents, and supporting records required by cooperatives. This system produces the output of Credit Application Letters, Sales Reports, Accounts Receivable Reports, Payment Reports, Official Notes, and Journals. Keywords: Accounting System, Cooperative, Sales, Credit